The Determinants of China’s Commercial Banks: Does the Shareholding Reform Matter? - Huang, Meng (2009)
Abstract This paper analyses what are the determinants of China’s commercial bank performances, and whether shareholding reformation improves bank performance. Return on average assets (ROAA), return on average equities (ROAE) and net profit margin (NIM) are employed as a measure of bank performance, individually. I investigate the unbalanced panel data of 17 China national commercial banks, includes the “big four” SOCBs and 13 national joint stock banks from 2001 to 2008. Two models are established. To estimate these two models, both fixed/ random effect approach, and system GMM approach are employed. I find that, for both models, cost to income ratio, equity to total assets ratio, and loan loss reserve to gross loans ratio are important determinants of bank performance when I employ ROAA and NIM as a indictor of bank performance. Macroeconomic economic environments influence the bank performance in the form of net interest margin. However, so far, the results indicate that shareholding reform does not produce any strong or marked effect on bank performance in China as I expect.